Role of health professionals in the early detection and treatment of neonatal jaundice (Research, Society and Development, 2022)
The present study aimed to identify the actions of professionals in the early detection and treatment of neonatal jaundice. The present research is an integrative literature review, which consists of broader methodological approaches among the literature reviews. Thus, steps were carried out: 1- Elaboration of the guiding question; 2- Sampling of literature; 3- Data collection; 4- Critical analysis of the included studies; 5- Discussion of the results; 6- Presentation of the review/conclusion. Thus, it was possible to structure the guiding question: “What are the actions of health professionals in the early detection and treatment of neonatal jaundice?”. recommendations are made regarding the screening of newborns for jaundice before hospital discharge, the performance of the transcutaneous bilirubin test or total serum bilirubin, however, the TSB should be measured in all newborns who presented jaundice in the first 24 hours of life and also in those with excessive jaundice for their age. Finally, the study was so important in the need for further research developments on the subject in question, due to the scarcity of conducts, studies and diversity of strategies pertinent to the procedures performed for the early detection and treatment of neonatal jaundice. However, it was also possible to present that a clinical route, the investment of knowledge for non-specialized professionals and some collection of information regarding the characteristics of feces, membranes and mucous membranes, can lead to an early diagnosis of neonatal jaundice.